A robust color image watermarking with Singular Value Decomposition method - Dogan, Sengul; Tuncer, Turker; Avci, Engin; Gulten, Arif (Elsevier Sci Ltd, 2011)
The performance of a watermarking method based on Singular Value Decomposition (SVD) has been improved for color image in this paper. One of the common methods used for hiding information on image files is Singular Value Decomposition method which used in the frequency domain. In Singular Value Decomposition based watermarking techniques; watermark embedding can usually be achieved by modifying the least significant bits of the singular value matrix. This paper gives application results which show the watermarking security of using this algorithm for the watermarking and demonstrate the accuracy of these methods. The performance comparison of the algorithms was also realized. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Watermarking; Multi-modal biometric; Singular Value Decomposition (SVD); Color image; Data hiding; Data security